KEPASTIAN HUKUM PUTUSAN BANDING ADMINISTRATIF DALAM PENYELESAIAN SENGKETA ADMINISTRASI TATA USAHA NEGARA - Nugroho, Purwo Adi; ARWANTO, BAMBANG (Fakultas Hukum Universitas Narotama, 2026)
Legal certainty is one of the main principles in the rule of law system that requires every action and decision made by government administration to be based on clear, understandable law, and provides a guarantee of protection for the rights of citizens. In resolving disputes in the field of state administrative administration, one of the procedures regulated is through administrative mechanisms in the form of filing objections and administrative appeals. This study aims to examine whether an administrative appeal decision can still be pursued further legal remedies, as well as how the principle of legal certainty is realized in the process using normative research methods with a statue approach and conceptual approach. The results of the study show that administrative appeal decisions are final in the realm of government administration, so that no objection or re-appeal is possible administratively. However, this finality does not eliminate the right of individuals to file a lawsuit with the State Administrative Court (PTUN) if they feel aggrieved. The judicial route remains open as a form of judicial oversight of administrative actions. Keywords: Legal Certainty, Administrative Appeal Decision, State Administration